Effect of Priangan ram seminal plasma on viability of Peranakan Etawah buck spermatozoa preserved at 3–5oC - Muhammad Rizal; Herdis .; Maman Surachman; W. Marlene Mesang-Nalley (Indonesian Center for Animal Research and Development (ICARD), 2008)
In processing of buck semen, seminal plasma is a problem because it contains a phospholipase A enzime produced by the Cowper gland. If this enzime interacts with egg yolk, it causes semen coagulation, and consequently death of spermatozoa. The purpose of this research was to examine the effect of Priangan ram seminal plasma on viability of Peranakan Etawah (PE) buck spermatozoa preserved at 3–5oC. Semen was collected using artificial vagina once a week. Fresh semen was divided into three tubes then centrifuged at 3,000 RPM for 30 min. Supernatant of the first tube was mixed again with Pasteur pipette (treatment A or control). Supernatant of the second tube was removed (treatment B or without seminal plasma). Supernatant of the third tube was removed and changed with Priangan ram seminal plasma in the same volume (treatment C). Semen was diluted with Tris extender containing 20% egg yolk and stored in refrigerator at 3–5oC. Quality of diluted-semen including percentages of motile spermatozoa (MS), live spermatozoa (LS), and intact plasma membrane (IPM) was evaluated every day during storage at 3–5oC for three days. Results of this study showed that mean volume, colour, consistency, pH, mass activity, spermatozoa concentration, MS, LS, spermatozoa abnormal, and IPM of PE buck fresh semen, respectively was 0.68 ml, cream, thick, 7, ++/+++, 4,148.57 million cell/ml, 70%, 83.89%, 7.12% and 84%. At day-4 of storage, percentages of MS, LS, and IPM for treatment C (40, 52.2 and 51.6%) was significantly (P<0.05) higher than that of: treatment B (31, 44.8 and 45.2%) and treatment A (11, 15.6 and 14.8%). In conclusion, seminal plasma of Priangan ram could maintain the quality of PE buck semen preserved at 3–5oC for three days, and it prevent semen from coagulation. Key Words: Seminal Plasma, Priangan Ram, Spermatozoa Viability, PE Buck